Sap Crm as A Central Engine for Hybrid Trade Promotion Management in Post-Acquisition Integration Scenarios - Vinayak Kalabhavi (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
The issue of disparity between the heterogeneous trade promotion management systems and processes arises in the post-acquisition integration scenarios in the Consumer-Packaged Goods (CPG) industry. This paper will examine the role of SAP Customer Relationship Management (CRM) as a hub for implementing hybrid trade promotion models under the managerial process in organisational integration. The results of implementation were discussed through the set of post-acquisition experiences when SAP CRM served as the platform for the integration of trade promotion processes, which previously were handled differently. Findings suggest that the SAP CRM hybrid architecture will support a 67 percent improvement in promotion effectiveness and will also save 45 percent of integration complexity in the period that is crucial after the acquisition process. This analysis goes further to illustrate that organisations that use SAP CRM as the core trade promotion engine in the case of mergers and acquisitions realise a three-year payback of 306% and a 23% CRM promotional planning shortening. Integration tasks that are mainly addressed are harmonisation of master data, promotional workflow standardisation, as well as performance analytics consolidation of different organisational structures. The hybrid model enables organisations to maintain continuity in their operations and gradually adopt standardised workflows, which will nullify the integration risks and speed the value creation. In turn, the given research contributes to the knowledge about how the use of enterprise systems is a key enabling factor in the face of the most complicated organisational changes and the provision of tangible business value.